Catalytic Asymmetric Amino Acid and Its Derivatives by Chiral Aldehyde Catalysis - Lin, Kaijin; Shi, Ang; Shi, Chunhong; Lin, Jinbiao; Lin, Honggui (Frontiers in Chemistry, 2021)
Amine acid transformation is an important chemical process in biological systems. As a well-developed and acknowledged tool, chiral aldehyde catalysis provides good catalytic activation and stereoselective control abilities in the asymmetric reaction of N-unprotected amino acid esters and amino acid esters analogs, in which the key to success is the design of the catalysts derived from chiral BINOL aldehyde, which is based on the face control of enolate intermediates. In this review, one of the co-catalytic systems that combined with a transition metal to form a multiplex catalytic system and the well-established multiplex stereocenters of chiral aldehyde catalysis have been reviewed. Finally, a novel organocatalysis is prospected.